A Decadal Evaluation of Mandatory CSR in India: Evidence from BSE-500 Firms and SDG Linkages (2014–2024) (American Journal of Economics and Business Innovation, 2025)
This study presents a comprehensive decadal analysis (2014–2024) of Corporate Social Responsibility (CSR) implementation among India’s top 500 BSE-listed companies following the enforcement of Section 135 of the Companies Act, 2013. As the first country to mandate corporate social responsibility (CSR) by law, India presents a unique landscape for evaluating the evolution of corporate social spending behavior, compliance patterns, and alignment with national development priorities and the Sustainable Development Goals (SDGs). The paper adopts a mixed-methods approach combining quantitative trend analysis, quadrant mapping, regression models, and qualitative NVivo-style insights. The findings reveal four distinct phases of CSR evolution: initial under-compliance (2014–2016), rising obligations with spending lag (2016–2018), over-compliance with moderate obligations (2018–2020), and mature CSR performance with consistent overspending (2020–2024). Statistical evidence confirms a significant positive relationship between CSR obligations and actual spending, while sectoral allocation remains concentrated in education and health, collectively accounting for over 60% of total CSR expenditure. SDG mapping reveals strong corporate alignment with SDGs 3, 4, and 8; however, it highlights persistent underinvestment in climate action (SDG 13), gender equity (SDG 5), and innovation (SDG 9). Qualitative insights based on stakeholder perceptions uncover implementation challenges, including top-down planning, cultural misalignment, and weak monitoring, especially in underdeveloped regions such as North-East India. The paper also benchmarks India’s CSR framework against global models from China, the UK, and Brazil, illustrating both the strengths and gaps of India’s mandatory regime. The study concludes with targeted policy recommendations to shift from compliance-focused CSR to outcome-oriented, SDG-linked, and regionally balanced strategies. By blending robust data analysis with stakeholder perspectives and policy implications, this paper contributes to the evolving discourse on CSR governance, sustainability integration, and corporate accountability in emerging economies.